2021
DOI: 10.1108/ijchm-02-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsible human resource practices and hospitality employee outcomes

Tuan Trong Luu

Abstract: Purpose This paper aims to unfold the mediation mechanism of job crafting, through which socially responsible human resource practices (SRHR practices) influence work meaningfulness and job strain among hospitality employees. It also seeks to unravel the moderating effect of authentic leadership on this indirect relationship. Design/methodology/approach Three survey waves were conducted to collect data from 825 employees and 128 managers from 34 four- or five-star hotels in two major cities in Vietnam. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 176 publications
(247 reference statements)
3
46
0
Order By: Relevance
“…Such factors include firms' strategic policies and priorities [48,60], available financial resources [60], HRM systems design [60], HRM power in the organization [26], ethics-oriented HRM philosophies [65], the multi-nationality of firms [93], as well as organizational structure and culture [80]. The third antecedent category is related to the individual factors, including employees' needs and wants [21,62,77,79], the presence of an ethical leader [60,61,75,89,92,101], the HR professionals' perception of their ethical role [61], and the role of employees' representatives in organizations [56].…”
Section: Antecedents Of Srhrmmentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors include firms' strategic policies and priorities [48,60], available financial resources [60], HRM systems design [60], HRM power in the organization [26], ethics-oriented HRM philosophies [65], the multi-nationality of firms [93], as well as organizational structure and culture [80]. The third antecedent category is related to the individual factors, including employees' needs and wants [21,62,77,79], the presence of an ethical leader [60,61,75,89,92,101], the HR professionals' perception of their ethical role [61], and the role of employees' representatives in organizations [56].…”
Section: Antecedents Of Srhrmmentioning
confidence: 99%
“…Other individual factors positively affected by SRHRM practices include employee citizenship behavior [51,55,62,66,83,84,92], employee task performance [59,94], employee satisfaction [72,81,95], employee well-being [68,78], employee loyalty [101], the propensity of employees to identify themselves with their organization [59,83,88,89,91], employeeemployer relationships [79,84], employee trust in the firm [72,74,76], employee empathy [52], employee knowledge sharing behavior [74], employee innovation behavior [54,99], and employee intrapreneurial behavior [96,98,99]. It has also been shown that SRHRM practices can help employees to make sense of their jobs in a meaningful way [75] and even make employees more resilient in times of crisis, such as during the COVID-19 pandemic [76]. Further positive outcomes include increasing employee advocacy behavior within social media platforms [84] and enhancing the person-organization fit [69].…”
Section: Outcomes Of Srhrmmentioning
confidence: 99%
“…Our research mainly focuses on consumers' reactions to CSR, and thus it provides few insights on this issue. But a key finding in extant CSR and employee literature is that CSR initiatives make employees feel their job is significant (Kim et al, 2018) and increase their self‐esteem (Luu, 2021). But whether these results can be generalized to the luxury hospitality sector awaits future research.…”
Section: Discussionmentioning
confidence: 99%
“…As explained in our justification for hypothesis 2a, responsible leadership may be a promoter of SRHRM. Furthermore, resources gained from SRHRM can translate to pride in organizations (Luu, 2021), which subsequently motivates employees to exhibit more innovative behavior as we discussed in hypothesis 3b. To integrate the hypotheses introduced above, we further posit the sequential mediating effects of SRHRM and organizational pride.…”
Section: The Sequential Mediation Mechanismmentioning
confidence: 91%